2017
DOI: 10.17576/ajag-2017-08si-11
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology Usage, Top Management Support and Internal Audit Effectiveness

Abstract: There has been a marked increase in the global

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…They claim firms are expected to have adequate internal control system to have an appropriate WCM. Prior studies have suggested the importance to have management support on internal control system and technology implemented to ensure the effectiveness of internal audit function (for examples, Hassan et al 2015;Alkebsi & Aziz 2017). Nevertheless there are lack of empirical evidence on the relationship between internal audit investment and WCM.…”
Section: Internal Auditing and Cash Conversion Cycle (Ccc)mentioning
confidence: 99%
“…They claim firms are expected to have adequate internal control system to have an appropriate WCM. Prior studies have suggested the importance to have management support on internal control system and technology implemented to ensure the effectiveness of internal audit function (for examples, Hassan et al 2015;Alkebsi & Aziz 2017). Nevertheless there are lack of empirical evidence on the relationship between internal audit investment and WCM.…”
Section: Internal Auditing and Cash Conversion Cycle (Ccc)mentioning
confidence: 99%
“…Management of the organizations allows internal audit to use new software technologies and expects its work to be higher quality. There was a research that found the correlation between the importance of technology usage and performance of internal audit; in addition there was a positive relationship between management support and internal audit effectiveness (Alkebsi & Aziz, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Internal audit is a systematic process and a disciplined approach to assessing and enhancing the effectiveness of risk management and control [3], [19], [32]. It is a governance process that determines the organisational performance against noncompliance, errors, and inefficiencies [35]. Effective internal audit includes audit planning, execution, and reporting on the audit findings [10].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The audit team should be knowledgeable about the people and processes to be audited and skilled in analysing logic, evaluating business data and processes, and communicating at all levels within the organisation [19]. In strengthening the skills and the credibility of the internal audit team, technical competencies and ongoing training are essential as the basis for effective internal audit [35]. Continuous improvements should be implemented to ensure that incidents, threats, and risks are always controlled.…”
Section: Literature Reviewmentioning
confidence: 99%